THE RELATIONSHIP OF KNOWLEDGE WITH ADOLESCENT MEDICINE COMPLIANCE WITH PULMONARY TUBERCULOSIS IN THE PEDIATRIC OUTPATIENTS DEPARTMENT, SUBANG DISTRICT - Nuraeni, Ade; Lesmana, Reza Nanda; Fauziah, Wardah; Efendi, Adhan (Journal of Vocational Nursing, 2022)
Introduction: The increase in the number of Tuberculosis sufferers is caused by various factors, namely the lack of patient compliance for treatment and taking medication, expensive drug prices, the emergence of multiple resistances, lack of host resistance to mycobacteria and reduced bactericidal power of existing drugs. It also has other negative impacts, socially stigmatized and ostracized by the community. Methods: This research is quantitative type. The design of this research is design used in this research, which is a cross-sectional design with observation or data collection at once (point time approach). The sample in this study was 20 people. The sampling technique used in this study was census sampling, this research data collection used a questionnaire measuring instrument, and the data analysis used the chi-square test. Results: the results of the analysis showed a significant degree of p < 0.000 by setting the degree of significance <0.005; thus, the conclusion is that there is a relationship between knowledge and adherence to drinking pulmonary tuberculosis in adolescents. Conclusions: there is a relationship between knowledge and adherence to drinking pulmonary tuberculosis in adolescents at the pediatric outpatients department at the District Hospital Subang.